2010
DOI: 10.1128/jcm.01232-10
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial 16S Sequence Analysis of Severe Caries in Young Permanent Teeth

Abstract: Previous studies have confirmed the association of the acid producers Streptococcus mutans and Lactobacillus spp. with childhood caries, but they also suggested these microorganisms are not sufficient to explain all cases of caries. In addition, health-associated bacterial community profiles are not well understood, including the importance of base production and acid catabolism in pH homeostasis. The bacterial community composition in health and in severe caries of the young permanent dentition was compared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
288
8
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(336 citation statements)
references
References 49 publications
32
288
8
8
Order By: Relevance
“…Further, expression of the gene in question and successful translation may not be efficient in the E. coli host since some gram-positive proteins are toxic when translated within E. coli . An alternative explanation might be the limitations of the samples and method: (i) Studies have confirmed that S. mutans is not the only predominant caries-pathogenic bacterium [14,15]; depending on individual patients, it might not be the principal ECC bacterium [42]. Hence, in this study, the abundance of S. mutans might only occupy a small fraction of the collected caries samples, limiting the genetic information in our library and reducing the chance of obtaining functional genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, expression of the gene in question and successful translation may not be efficient in the E. coli host since some gram-positive proteins are toxic when translated within E. coli . An alternative explanation might be the limitations of the samples and method: (i) Studies have confirmed that S. mutans is not the only predominant caries-pathogenic bacterium [14,15]; depending on individual patients, it might not be the principal ECC bacterium [42]. Hence, in this study, the abundance of S. mutans might only occupy a small fraction of the collected caries samples, limiting the genetic information in our library and reducing the chance of obtaining functional genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent high-throughput sequencing studies based on culture-independent analysis of childhood caries revealed that S. mutans is not the only dominant pathogenic bacterium in caries. Lactobacillus, Selenomonas and Neisseria can also be detected at high levels in severe carious plaques [14,15], and some of these bacteria cannot be cultured (Human Oral Microbiome Database (HOMD), http://www.homd.org/). In addition to Streptococcus , our knowledge about the acid resistance and related regulatory genes of cariogenic microorganisms, especially those that are not cultivable, is limited; thus, it offers a fertile field for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Recent molecular study using second-generation sequencing and metagenomic techniques has discovered an extraordinary ecosystem where S. mutans accounted for only 0.7-1.6% of carious lesions. [10,33] However, some recent studies indicate that the relationship between S. mutans, and caries is not absolute high proportions of S. mutans may persist on tooth surfaces without lesion development, and caries can develop in the complete absence of S. mutans. [34,35] Veillonella are an acidogenic Firmicutes with 5.8% of the total population.…”
Section: Discussionmentioning
confidence: 99%
“…This includes S. mutans, non-mutans Streptococci and members of the genera Actinomyces, Bifidobacterium, L.bacillus, Propionibacterium, Veillonella, Selenomonas, and Atopobium are associated with different stages of carious lesions. [7][8][9][10] Low environmental pH was due to shift of an acid-tolerant and acid-producing consortium of bacteria, which altered the balance of remineralization to demineralization, thus forming the carious lesions. [11] The size and thickness of the lesion was also correlated with the initial pH.…”
Section: Introductionmentioning
confidence: 99%
“…However, no previous studies have evaluated the antimicrobial activity exclusively against bacterial strains of deep decayed dentin [16][17] .…”
Section: Discussionmentioning
confidence: 99%